Development and Verification of a Combined Immune- and Metabolism-Related Prognostic Signature for Hepatocellular Carcinoma - Guo, Yuanyuan; Yang, Jing; Gao, Hua; Tian, Xin; Zhang, Xiaojian; Kan, Quancheng (Frontiers in Immunology, 2022)
Immune escape and metabolic reprogramming are becoming important characteristics of tumor biology, which play critical roles in tumor initiation and progression. However, the integrative analysis of immune and metabolic characteristics for the tumor microenvironment remains unclear. Herein, by analyzing univariate and lasso Cox regressions, a prognostic signature associated with tumor microenvironment was established based on five immune- and metabolism-related genes (IMRGs), which was fully verified and evaluated in both internal and external cohorts and the C-index was superior to other HCC signatures, indicating the robustness and reliability of IMRGs prognostic signature. A nomogram was built based on IMRGs prognostic signature and various clinical parameters, such as age and T stage. The AUCs of nomogram at 1-, 3- and 5-year (AUC=0.829, 0.749, 0.749) was slightly better than that of IMRGs signature (AUC=0.809, 0.734, 0.711). The relationship of risk score (RS) with immune checkpoint expressions, four IPS scores, as well as MSI together accurately predicted the treatment efficacy. Collectively, the IMRGs signature might have the potential to better predict prognostic risk, evaluate immunotherapy efficacy and help personalize immunotherapy for HCC patients.